On the Main Regulatory Characteristics of the Natura 2000 Network in EU Law and Hungarian Law - Klara Bak (European Scientific Journal, ESJ, 2026)
The Natura 2000 ecological network established in the European Union has grown into a particularly large network in the 27 Member States of the EU, which is of inestimable importance for the conservation of biodiversity. The regulation can be described as two-tiered in relation to the EU and the Member States. EU law sets out framework rules in its relevant directives. It contains specific classifications in its annexes for animal and plant species and areas of Community importance that require protection. On this regulatory foundation, Member States must enact appropriate legislation that is practical to apply and takes into account the specific characteristics of the given State. Considering the significance of Natura 2000 sites, this paper first aims to analyse the main provisions of the relevant EU regulations, then to present the regulatory framework and content of Hungarian national law concerning Natura 2000 sites. The thesis suggests that, because of the unique features of the regulatory field, a complex, multi-tiered regulatory approach is justified. Achieving the best protection for nature requires detailed regulation, which is most suitably carried out at a lower legislative level.